Frequency of urinary tract infections among pregnant women receiving antenatal care in a tertiary care centre: hospital based cross-sectional study - Sadhvi, Kumari; Kose, Varsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Urinary tract infections (UTI) are one of the most frequent human bacterial infections, causing substantial morbidity and mortality, with nearly 150 million cases globally per year. The prevalence of UTI (including both asymptomatic bacteriuria and symptomatic infection) in pregnant women in India is reported to range from 3% to 24%. This infection must be adequately diagnosed and efficient treatment must be initiated to prevent maternal and perinatal morbidity. Methods: This was a hospital based cross sectional study. 625 ante natal women recruited during first visit attending antenatal care outpatient department (ANC OPD). We tested their clean catch mid-stream urine sample for routine, microscopic and culture sensitivity test. Results: Out of 625 antenatal women frequency of urinary tract infection was 16.2%. 17% women were symptomatic having one or more symptoms indicative of urinary tract infection and 83% women were asymptomatic. Among symptomatic women, 92.5% women showed culture positivity for one or more bacteria whereas in asymptomatic women, culture was positive in 10.8%. E. coli followed by Klebsiella were the most common isolate identified in both symptomatic and asymptomatic women. On antibiotic sensitivity testing, we found good overall sensitivity of bacteria to commonly used antibiotics such as nitrofurantoin, and norfloxacin but resistant to ampicillin was observed in all women. UTI adversely affects the mother like pyelonephritis, preterm labour and preterm baby and its complications. Conclusions: It is important to identify presence of UTI during pregnancy by doing urine routine and culture sensitivity test in all antenatal women and administration of appropriate antibiotic to affected women so as to reduce the morbidity both in mother and baby.